THE COPYRIGHT INFRINGEMENT IN USING FAMOUS ARTISTS NAMES AS FAN-FICTION NOVELS' CHARACTERS: A Juridical Analysis Based on Law No. 28/2014 Regarding of Copyrights - Nurani, Juli; Sari, Nuraini Kartika (jfpublisher, 2022)
Fan-fiction novel is one of the copyrighted works that already exist and are widely distributed on the internet. Generally, it is written by some fans in conveying their ideas and imagination about their idols and their ideas in the form of written works. There are many fan-fiction novels that have been commercialized or sold freely and massively in bookstores and certain application platforms throughout Indonesia. This brought some problems, one of those problems is using the artist's name as a character in its fan-fiction novel, which in its use, neither the author nor the publisher asked for permission to use their artist’ names. However such actions committed by authors and publishers is a deprivation of economic and moral rights from an artist as an entertainer in Law No.28/2014 concerning Copyright. The form of protection that can be given to famous artists and related parties can be in the form of preventive and repressive legal actions in accordance with Law No.28/2014 concerning of Copyright.